IDENTIFIKASI JENIS CACING SOIL TRANSMITTED HELMINTH (STH) PADA FESES PEKERJA PENGANGKUT SAMPAH KOTA KENDARI DENGAN METODE MODIFIKASI HARADA MORI DAN METODE MODIFIKASI KATO KATZ - Arimaswati Arimaswati; La Ode Alifariki; Faning Fridayani; Jamaluddin jamaluddin (Medika Respati : Jurnal Ilmiah Kesehatan, 2020)
Background: helminthiasis is classified as negleted disease, which is an infection that is not considered and is chronic without causing clear clinical symptoms and its effects can only be seen in the long term. Objective: to identify the types of worms in the feces of Kendari garbage transportation workers. Methods: uses laboratory observation methods to identify the type of Soil that is Contagious. Using 42 stool samples that have been stored for ± 2 months were taken from the stools of Kendari municipal waste workers and examined using the modified kato-katz, Harada Mori and Direct slide methods. Results: the results of various inspection methods namely, direct slide, Kato-katz modification and Harada Mori modification. Identification of the egg stage, the p-value is 0.002 <α = 0.05. This shows that the Kato-katz method is far better than the direct shear method in the examination of STH worm eggs. The p-value results in the examination of Harada mori larvae and the direct shear value were 0.001 <α = 0.05. This shows that the Harada mori method is better at identifying fecal larvae than the direct glide method. The Kato-Katz modification method is more effective in identifying the type of worm egg than the direct slide method. The most common type of Transmitted Helminth earthworm identified in this study is hookworm. Conclusion: The Kato Katz method is a better method used than the direct slide method in identifying the type of Soil transmitted Helminth (STH) in the egg phase. Harada mori is a better method used than the direct slide method in identifying the type of Soil transmitted Helminth (STH) worm in the larval phase. The type of STH worm most identified in this study is the hookworm.